Tendon extracellular matrix damage, degradation and inflammation in response to in vitro overload exercise. Issue 6 (June 2015) - Spiesz, Ewa M.; Thorpe, Chavaunne T.; Chaudhry, Saira; Riley, Graham P.; Birch, Helen L.; Clegg, Peter D.; Screen, Hazel R.C.
ABSTRACT The role of inflammation in tendon injury is uncertain and a topic of current interest. In vitro studies of tendon accelerated overload damage can serve as a valuable source of information on the early stages of tendinopathy. Viable fascicle bundles from bovine flexor tendons were subjected to cyclic uniaxial loading from 1–10% strain. Immuno‐staining for inflammatory markers and matrix degradation markers was performed on the samples after mechanical testing. Loaded samples exhibited visible extracellular matrix damage, with disrupted collagen fibers and fiber kinks, and notable damage to the interfascicular matrix. Inflammatory markers COX‐2 and IL‐6 were only expressed in the cyclically loaded samples. Collagen degradation markers MMP‐1 and C1, 2C were colocalized in many areas, with staining occurring in the interfascicular matrix or the fascicular tenocytes. These markers were present in control samples, but staining became increasingly intense with loading. Little MMP‐3 or MMP‐13 was evident in control sections. In loaded samples, some sections showed intense staining of these markers, again localized to interfascicular regions. This study suggests that inflammatory markers may be expressed rapidly after tendon overload exercise. Interestingly, both inflammation and damage‐induced matrix remodeling seem to be concentrated in, or in the vicinity of, the highly cellular interfascicular matrix. © 2015 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 33:889–897, 2015.